Bacterial cellulose from glucanacetobacter xylinus: Preparation, properties and applications - Pecoraro, Édison [UNESP]; Manzani, Danilo [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2008)
This chapter deals with the cellulose produced by the Glucanacetobacter xylinus strain, called bacterial cellulose, which is a remarkably versatile biomaterial usable in wide variety of domains, such as papermaking, optics, electronics, acoustics, and biomedical devices. Its unique structure shows entangled ultrafine fibers, which provide excellent mechanical strength, besides biodegradability, biocompatibility, high water-holding capacity, and high crystallinity. Some of its applications are described, such as complementary nutrition (. nata de coco), artificial temporary skin for wounds and burns, dental aid, artificial blood vessels and micronerve surgery, DNA separation, composite reinforcement, electronic paper, light emitting diodes, and fuel cell membranes. © 2007 Elsevier Ltd. All rights reserved.